Punishing Dangerousness: Cloaking Preventative Detention as Criminal Justice - Robinson, Paul H. (2001)
Laypersons have traditionally thought of the criminal justice system as being in the business of doing justice: punishing offenders for the crimes they commit. Yet during the past several decades, the justice system's focus has shifted from punishing past crimes to preventing future violations through the incarceration and control of dangerous offenders. Habitual-offender statutes, such as three strikes laws, authorize life sentences for repeat offenders. Jurisdictional reforms have decreased the age at which juveniles may be tried as adults. Gang membership and recruitment are now punished. Megan's Law statutes require community notification of convicted sex offenders. Sexual predator statutes provide for the civil detention of sexual offenders who remain dangerous at the conclusion of their criminal commitment. New sentencing guidelines increase the sentence of offenders with criminal histories because these offenders are seen as the most likely to commit future crimes. These reforms boast as their common denominator greater official control over dangerous persons, a rationale readily apparent from each reform's legislative history. Although the individual legislative histories make clear that a preventive rationale has motivated each of these reforms, the system's general shift from punishment toward prevention has not been accompanied by a corresponding shift in how the system presents itself. While increasingly designed to prevent dangerous persons from committing future crimes, the system still alleges that it is doing criminal justice and imposing punishment. Yet it is impossible to punish dangerousness. To punish is to cause (a person) to undergo pain, loss, or suffering for a crime or wrongdoing --therefore, punishment can only exist in relation to a past wrong. Dangerous means likely to cause injury, pain, etc. --that is, dangerousness describes a threat of future harm. One can restrain, detain, or incapacitate a dangerous person, but one cannot logically punish dangerousness. Why the shift to preventive detention? Why the wish to keep the old criminal punishment facade? These are the starting points of inquiry in this Commentary. It concludes that the trend of the last decade--the shifting of the criminal justice system toward the detention of dangerous offenders--is a move in the wrong direction. The difficulty lies not in the laudable attempt to prevent future crime but rather in the use of the criminal justice system as the vehicle to achieve that goal. The approach perverts the justice process and undercuts the criminal justice system's long-term effectiveness in controlling crime. At the same time, the basic features of the criminal justice system make it a costly yet ineffective preventive detention system. Available for download at http://ssrn.com/abstract=18328